(untitled) (TECHNO REVIEW. International Technology, Science and Society Review /Revista Internacional De Tecnología, Ciencia Y Sociedad, 2023)
The research values the similarity between the theory of modernization (Americanization-Europeanization) and Chinaticization as an expansionist model in Latin America and the Caribbean (LAC). The study is qualitative to characterize the Chinaticization phenomenon through the trade flow data (import-export) and foreign direct investment to assess the impact on gross domestic product (GDP) and employment in LAC. The results show a deficit in the trade flow of China, a high trend in imports from the primary sector and exports from the secondary. Chinese investment and GDP in LAC show an upward trend with a slowdown in addition to an insignificant impact on employment.